Impact of soil use on aggregate stability and its relationship with soil organic carbon at two different altitudes in the Colombian Andes (2019)
The stability of soil aggregates depends on the organic matter, and the soil use and management can affect the soil organic matter (SOM) content. Therefore, it is necessary to know the relationship between aggregate stability and the content of SOM in different types of soil use at two different altitudes of the Colombian Andes. This study examined the conditions of soil aggregate stability expressed as a distribution of the size classes of stable aggregates (SA) and of the mean weighted diameter of the stable aggregates (MWD). To correlate these characteristics with the soil organic carbon (OC), we measured the particulate organic matter pool (POC), the OC associated with the mineral organic matter pool (HOC), the total organic carbon content (TOC), and the humification rate (HR). Soils were sampled at two altitudes: 1) Humic Dystrudepts in a cold tropical climate (CC) with three plots: tropical mountain rainforest, pastures, and crops; 2) Fluvaquentic Dystrudepts in a warm tropical climate (WC) with three plots: tropical rainforest, an association of oil palm and pastures, and irrigated rice. Soils were sampled at three depths: 0-5, 5-10 and 10-20 cm. The physical properties, mineral particle size distribution, and bulk density were measured. The content of SA with size>2.36 mm was higher in the CC soil (51.48%) than in the WC soil (9.23%). The SA with size 1.18-2.36 mm was also higher in the CC soil (7.78%) than in the WC soil (0.62%). The SA with size 0.60-1.18 mm resulted indifferent. The SA with size between 0.30 and 0.60 mm were higher in the WC soil (13.95%) than in the CC soil (4.67%). The SA<0.30 mm was higher in the WC soil (72.56%) than in the CC soil (32.15%). It was observed that MWD and the SA>2.36 mm increased linearly with a higher POC, but decreased linearly with a higher HR. For the SA<0.30 mm, a linear decrease was observed at a higher POC, while it increased at a higher HR.